The Analysis of Phonological Process on the English Consonant Sounds of Balinese EFL Students' Pronunciation - Cahyani Putri Utami; Kresna Cahyadi Putra (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. This phonological analysis investigated the production of English consonant sounds produced by Balinese EFL students’ who speak an idiosyncratic native language as the main phenomena and examined the phonological rules represented descriptively and qualitatively. The data were gathered through digital recording and were observed by identifying the English pronunciation through note taking technique. This study was supported by the theories regarding phonological rules proposed by Odden (2013) and Hayes (2008). The Oxford Advanced Learner's Dictionary was used as a standard form of American pronunciation to compare the sounds produced by the students. The result of the study shows that the phonological errors represented in two ways of phonological rules: assimilation and deletion. First, assimilation occurred in the three positions of the word in three different sounds: [z], [ð] and [?]. Second, final deletion of specific phoneme /k/ and the deletion of aspirated allophones of the phoneme /p/. This study provides a significant contribution that there are several common phonological errors of English consonant sounds encountered by Balinese EFL students.Keywords: English consonants, phonological process, phonological rule, pronunciationAbstrak. Penelitian ini bertujuan untuk menganalisis produksi bunyi konsonan bahasa Inggris yang diproduksi oleh mahasiswa EFL Bali yang memiliki bahasa ibu yang idiosinkratik sebagai fenomena utama dan menentukan aturan fonologis secara deskriptif dan kualitatif. Data dikumpulkan melalui rekaman digital dan diamati dengan mengidentifikasi pengucapan melalui teknik pencatatan. Teori kaidah fonologis yang dikemukakan oleh Odden (2013) dan Hayes (2008) digunakan dalam penelitian ini. Selain itu, Oxford Advanced Learner's Dictionary digunakan dalam mengidentifikasi standar pengucapan bahasa Inggris untuk membandingkan dengan pengucapan siswa. Hasil penelitian menunjukkan bahwa pengucapan Bahasa Inggris oleh siswa dapat direpresentasikan dalam dua kaidah fonologis. Pertama, proses asimilasi terjadi pada tiga posisi kata dalam tiga bunyi berbeda: [z], [ð] dan [?]. Kedua, penghapusan fonem akhir tertentu yakni fonem /k/ dan penghapusan alofon fonem /p/. Penelitian ini memberikan kontribusi yang signifikan bahwa terdapat beberapa kesalahan fonologis yang umum terjadi pada bunyi konsonan bahasa Inggris yang ditemui oleh mahasiswa EFL Bali.Kata kunci: bunyi konsonan bahasa Inggris, kaidah fonologis, pelafalan, proses fonologis